Recombinant Newcastle disease viruses expressing immunological checkpoint inhibitors induce a pro-inflammatory state and enhance tumor-specific immune responses in two murine models of cancer - Santry, Lisa A.; van Vloten, Jacob P.; AuYeung, Amanda W. K.; Mould, Robert C.; Yates, Jacob G. E.; McAusland, Thomas M.; Petrik, James J.; Major, Pierre P.; Bridle, Byram W.; Wootton, Sarah K. (Frontiers in Microbiology, 2024)
Tumor microenvironments are immunosuppressive due to progressive accumulation of mutations in cancer cells that can drive expression of a range of inhibitory ligands and cytokines, and recruitment of immunomodulatory cells, including myeloid-derived suppressor cells (MDSC), tumor-associated macrophages, and regulatory T cells (Tregs). To reverse this immunosuppression, we engineered mesogenic Newcastle disease virus (NDV) to express immunological checkpoint inhibitors anti-cytotoxic T lymphocyte antigen-4 and soluble programmed death protein-1. Intratumoral administration of recombinant NDV (rNDV) to mice bearing intradermal B16-F10 melanomas or subcutaneous CT26LacZ colon carcinomas led to significant changes in the tumor-infiltrating lymphocyte profiles. Vectorizing immunological checkpoint inhibitors in NDV increased activation of intratumoral natural killer cells and cytotoxic T cells and decreased Tregs and MDSCs, suggesting induction of a pro-inflammatory state with greater infiltration of activated CD8 + T cells. These notable changes translated to higher ratios of activated effector/suppressor tumor-infiltrating lymphocytes in both cancer models, which is a promising prognostic marker. Whereas all rNDV-treated groups showed evidence of tumor regression and increased survival in the CT26LacZ and B16-F10, only treatment with NDV expressing immunological checkpoint blockades led to complete responses compared to tumors treated with NDV only. This demonstrated that NDV expressing immunological checkpoint inhibitors could reverse the immunosuppressive state of tumor microenvironments and enhance tumor-specific T cell responses.